Primary care patient and practice member perspectives on weight loss medications: challenges and opportunities - Holtrop, Jodi Summers; Tietbohl, Caroline; Perreault, Leigh; Connelly, Lauri; Smith, Peter C.; Williams, Johnny (Frontiers in Medicine, 2025)
IntroductionObesity is a prevalent and concerning chronic condition; however, evidence-based interventions are available for treatment. With the arrival of newer and more effective anti-obesity medications, questions emerge regarding how these medicines can and should be used and how they affect the practice of primary care medicine. The objective of this study was to examine the many and intersecting factors affecting use and impact of these medicines.MethodsQualitative study of interviews with primary care practice members and their patients in one Colorado health system (n = 56 practices) over 3 years. Thematic analysis was used to triangulate responses from patients and practice members.ResultsKey themes from both practice members and patients were highly consistent revealing the following categories of benefits and burdens: (1) the new medicines are a “game changer” for practice and changed lives for patients, (2) there is significant burden for all in obtaining the medications for many patients, (3) not all patients should be on the medications, (4) the medications have changed the conceptualization of obesity for patients and providers, and practice teams, and (5) the availability of these medications have changed the practice of treating obesity in important ways. It was further identified that a cascade of events involving various factors with a “right fit” between the patient, provider, and other factors were needed to make way for access to and effective use of these medications.DiscussionThe arrival of highly effective weight loss medications may invigorate efforts to integrate weight management into primary care, but the implications of this shift are still unknown. Further exploration of the long-term effects on patients, providers and care paradigms is warranted.